2008
DOI: 10.1186/1472-6882-8-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus acidophilus supernatants on body weight and leptin expression in rats

Abstract: Background: Lactobacillus extracts and supernatants have been used as probiotics in human and veterinary medicine for their ability to enhance wound healing and immunity. Previous data from our laboratory demonstrated that Lactobacillus supernatant (LS) stimulated wound healing, angiogenesis and proliferation of embryonic cells after topical application. This current study shows that LS after its administration into the cerebral ventricles of male rats exerts systemic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 24 publications
(37 reference statements)
0
24
0
Order By: Relevance
“…LS also modulated the expression or release of other peptides involved in metabolism and body weight control. 99 Kimchi LAB plus kimchi raw materials and fermented products have also shown antiobesity effects. Especially, optimally ripened kimchi significantly decreased body fats and body weights of animals 3 and humans.…”
Section: Antiobesity Effect Of Kimchi Labmentioning
confidence: 98%
See 1 more Smart Citation
“…LS also modulated the expression or release of other peptides involved in metabolism and body weight control. 99 Kimchi LAB plus kimchi raw materials and fermented products have also shown antiobesity effects. Especially, optimally ripened kimchi significantly decreased body fats and body weights of animals 3 and humans.…”
Section: Antiobesity Effect Of Kimchi Labmentioning
confidence: 98%
“…The fermented soymilk significantly decreased plasma LDL cholesterol in HFD-induced obesity in SD rats. 98 Sousa et al 99 reported that administration of Lactobacillus supernatants (LS) into the brains of rats resulted in weight loss without a decrease in food consumption, but with simultaneous increases of leptin expression in neurons and peripheral adipose tissue. LS also modulated the expression or release of other peptides involved in metabolism and body weight control.…”
Section: Antiobesity Effect Of Kimchi Labmentioning
confidence: 99%
“…Lactobacillus strains are able to survive in the presence of bile and 164 low pH. Thus, Lactobacillus species survive throughout the gastrointestinal tract, including in 165 the stomachs, duodena, jejuna and colons, of animals and humans [70][71][72][73]. Hence, 166 Lactobacillus spp.…”
mentioning
confidence: 98%
“…Another study also report leptin level was reduced by a combined bifidobacteria (B. pseudocatenulatum SPM 1204, B. longum SPM 1205, and B. longum SPM 1207) in obese rats [58]. Interestingly and controversially, direct injection of Lactobacillus acidophilus supernatants (germ free) into the brains of rats lead to weight loss with an increase in leptin expression in neurons and adipose tissue [59].…”
Section: Leptinmentioning
confidence: 97%